THE USE OF REMOTELY PILOTED AIRCRAFT SYSTEMS BEYOND VISUAL RANGE FOR THE ASSESSMENT OF THE PRESENT SITUATION IN TERMS OF THE PROTECTION OF CRITICAL INFRASTRUCTURE AT THE EXAMPLE OF AUSTRIA - Grundner Peter (2017)
In this thesis, the author investigates the legal framework for the general flight operations using Remotely Piloted Aircraft Systems (RPAS) beyond visual Range (BVR). He concludes that currently only military RPAS can be used to protect critical infrastructure in Austria conveniently. This protection can be made after an assistance request even from the Austrian Armed Forces (AAF). It is exposed which authorities are entitled for such a request. In further steps, the limitations concerning the protection of privacy and data protection for an imaging sensor application used by military RPAS in Austria are described. Thus, the currently available military RPAS “Tracker” can be used in combination with other military aircraft but is separated from all civil airspace users. After the establishment of an air space restricted area the possibilities for creating a military airspace structure is graphically illustrated. A consideration of the economic viability, cost-benefit ratio and the rational handling of scarce resources between manned and unmanned aircrafts for reconnaissance missions is carried out using various examples. At the end of the thesis, the further planned development path integrating RPAS in the general flight operations is represented based on a milestone plan of the European Union (EU).